Reduced interhemispheric connectivity in traumatic brachial plexopathies after bionic reconstruction - Galia V Anguelova; Agnes Sturma; Oskar Aszmann; Mehmet S Yildirim; Anna Boesendorfer; Victor Schmidbauer; Karl-Heinz Nenning; Gregor Kasprian (NeuroImage)
Traumatic brachial plexus lesions (TBPL) can lead to permanent impairment of hand function despite timely brachial plexus surgical treatment. In selected cases with no recovery of hand function, the affected forearm can be amputated and replaced by a bionic hand to regain prehensile function. This cross-sectional study aimed to assess (sub)cortical motor activity and functional connectivity changes after TBPL and bionic reconstruction.Cortical activity was measured with functional MRI (fMRI) during execution, and imagery of hand closing movements with the affected and healthy arm and single subject analysis was performed on the fMRI data. An electromyography training session was performed before fMRI to ensure correct task performance. Additionally, functional connectivity, diffusion tensor imaging (DTI), and cortical thickness were analyzed.Six healthy controls (4 men, median age 27, range 22–54), three TBPL patients without prosthetic reconstruction (3 men, median age 50, range 19–58), and two TBPL patients with a prosthetic reconstruction (2 men, median age 41, range 40–41) were included. In patients, cortical activity in the premotor gyrus and supplementary motor cortex (SMC) was higher and more widespread during both actual and imagery movements of the affected as well as the unaffected arm. Moreover, patients showed increased interhemispheric functional connectivity from the most active voxel in the precentral gyrus and SMC in the actual movement task. Subcortical activation of the thalamus and pallidum was observed only in non-prosthesis patients during actual movements. Corticothalamic functional connectivity was increased mainly in patients without prosthesis during actual and imagery movements. There were no differences in cortical thickness between participants. TBPL patients showed fewer structural DTI-based interhemispheric connections between the left and right precentral gyrus and superior frontal gyrus than controls. Patients without prosthesis also exhibited fewer structural connections between the left and right thalamus and pallidum, whereas those with prosthesis demonstrated increased structural connectivity compared to controls.The increased and more widespread cortical activity and functional connectivity after TBPL may be due to increased central effort necessary for motor execution and planning, representing a compensation mechanism for the decrease of interhemispheric and subcortical connectivity. The initial loss of white matter may be counteracted by increased function and grey matter recruitment, which seems necessary even after white matter recovery later with prosthesis use. The clinical implication of our findings is that a selected group of TBPL patients may benefit from an earlier timing of bionic restoration of hand function.